Role of Confidence and Supply Chain Strategy during Legitimization of Justice in Countries of Transitional Period - Oksana Khotynska-Nor; Lidiia Moskvych; Alexey Yu. Mamychev; Yury V. Vasilyev; Svetlana I. Kuzina (International Journal of Supply Chain Management, 2019)
In recent years representatives of various sciences began to pay attention to the problems of legitimacy of power, making them the subject of scientific and political discussions by considering the supply chain strategy. At the same time, geopolitical changes in the world put on the agenda the search for effective ways of transition to democracy, which was the impetus to the development of the concept of